2022
DOI: 10.1186/s13018-022-03337-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of medial calcar support on proximal humeral fractures treated with locking plates

Abstract: Background Studies have reported mixed results on the importance of medial calcar support for the treatment of proximal humeral fractures. The purpose of this study was to compare radiographic and functional outcomes of patients who had displaced proximal humeral fractures with varying levels of medial support. Methods We performed a retrospective comparative cohort study. The study was conducted at a Level III trauma center in Taiwan. Seventy pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The IMCS can be inserted under direct vision attributable to the retractor's gentle longitudinal pull on the distal end of the proximal incision. Numerous studies in the literature had demonstrated that the success of plate xation of proximal humeral fractures was related to the insertion of IMCS to increase the medial column support [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…The IMCS can be inserted under direct vision attributable to the retractor's gentle longitudinal pull on the distal end of the proximal incision. Numerous studies in the literature had demonstrated that the success of plate xation of proximal humeral fractures was related to the insertion of IMCS to increase the medial column support [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the importance of an anatomical fracture reduction and fixation in order to reduce complications [ 15 , 16 ]. Different techniques such as fibular allografts [ 17 , 18 ], screw tip augmentation [ 19 , 20 ] and double plating [ 21 ] have been described to enhance medial calcar support [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of AVN after plating for proximal humeral fractures was as high as 68%, and even reached 80% in three- and four-part fracture cases [ 20 ]. The risk factors for humeral head necrosis after plating are related to the fracture type (AO type C and Neer four-part fractures), length of the dorsomedial metaphyseal extension, degree of fracture fragment displacement, and integrity of the medial hinge [ 16 , 21 ]. In this study, the rates of both AVN and screw cut-out after ORIF in patients ≥60 years of age were higher than those in patients <60 years, with an AVN rate of 19.4% and screw cut-out rate of 19.4% in the former, and 12.5% for AVN and 8.3% for screw cut-out in the latter.…”
Section: Introductionmentioning
confidence: 99%